1987
DOI: 10.1017/s0950268800061938
|View full text |Cite
|
Sign up to set email alerts
|

Q fever in the Netherlands: a sero-epidemiological survey among human population groups from 1968 to 1983

Abstract: SUMMARYA sero-epidemiological survey, using an indirect immunofluorescence test for IgG against Coxiella burnetii (phase II), was carried out in the Netherlands. Serum samples taken in 1968, 1975,1979 and 1983 were tested. Occupational groups with a supposedly high risk of infection (veterinarians, residents of dairy farms and taxidermists) showed a significantly higher percentage of seropositives than defined controls. The percentage of seropositive amateur wool spinners was significantly higher than that of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
3

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 7 publications
5
35
3
Order By: Relevance
“…In the same way, in other serological surveys in Europe, lower rates of seropositivity were observed, as it is illustrated by the following examples: in Switzerland, prevalences ranged from 27% [25] or 17% [26] reported for different rural areas to 10.9% recorded for urban areas [26]; in big cities of Germany and The Netherlands, the values were from 22% in 1968 to 31.3% in 1983 [27], and finally, readings as low as 5% and 6% were observed among blood donors coming from an endemic zone in southern France [28] and Portugal [29], respectively.…”
Section: Discussionsupporting
confidence: 61%
“…In the same way, in other serological surveys in Europe, lower rates of seropositivity were observed, as it is illustrated by the following examples: in Switzerland, prevalences ranged from 27% [25] or 17% [26] reported for different rural areas to 10.9% recorded for urban areas [26]; in big cities of Germany and The Netherlands, the values were from 22% in 1968 to 31.3% in 1983 [27], and finally, readings as low as 5% and 6% were observed among blood donors coming from an endemic zone in southern France [28] and Portugal [29], respectively.…”
Section: Discussionsupporting
confidence: 61%
“…Frequently exposed individuals may even remain asymptomatic. Thus, serological surveys of blood donors in Netherlands suggested that up to 73% of male donors were seropositive (19), suggesting that exposure to Q fever is widespread. However, in general, there are few reports of the disease and few patients are admitted to hospitals with acute Q fever, with the exception of some outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two (67 %) of these patients were probably infected in The Netherlands through contact with animals or animal products [17]. A survey in 1982/1983 among 432 persons, considered to be at high risk because of close contact with animals and animal products, showed high percentages (58 % in taxidermists to 84% in veterinarians) of seropositive responders with mainly IgG antibodies against C. burnetii phase-II antigen, indicating that Q fever had become endemic in The Netherlands [18].…”
Section: The Notification Of Infectious Diseases Started Inmentioning
confidence: 99%